Application of Accounting Data from ERP Systems of Business Entities in Logistics - Hanzal, Petr; Beranek, Roland (Communications - Scientific letters of the University of Zilina, 2016)
The aim of this paper is to introduce the methodology for application of accounting data of ERP systems, gained from business entities in the Czech Republic, in logistics. Every accounting file provides information about realized sales and purchases of each entity. With the help of accounting data it is possible to determine frequency and value of all sales and purchases. From the known address of the observed entity and its supplier and customer it is possible to derive the delivery distance. This logistic information can be analyzed and evaluated in charts. Although the result of the examination cannot be fully generalized due to a limited data source, it should be considered as the contribution to logistics studies in the broadest context.